Binary metal magnetic separable nanocomposite fiber and preparation method thereof

Through the use of frozen drying and water heat in magnetic nano-fiber composite materials, combined with urea and ammonia as a precipitant, the uniform preparation and efficient separation of dual metal magnetic nano composite fibers were successfully achieved. The problem improves the decentralization and magnetic performance of the materials.

CN116752249BActive Publication Date: 2025-01-24SUZHOU HELUO CLEAN ENERGY TECH RES INST CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310475649.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-28
Publication Date
2025-01-24
Estimated Expiration
2043-04-28

AI Technical Summary

Technical Problem

In the prior art, serious agglomeration and aggregation between magnetic nanoparticles limits their uniform dispersion and efficient application in magnetic nanofiber composite materials.

Method used

By using iron salt and another metal salt as a composite metal front -drive body, hybrid solution of water and alcohol as a solubitive, freezing and drying form a uniform composite metal salt, and use nano fiber as a carrier, urea and ammonia water as a precipitant, performed for permanent Water heat-烧 Burning method, realize the uniform preparation of binary metal magnetic nano-composite fibers.

Benefits of technology

The uniform dispersing and efficient separation of the dual metal magnetic nanoplastic fiber is realized, and the decentralization and magnetic properties of magnetic nanoparticles are improved, and it is suitable for industrialized production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116752249B_ABST
    Figure CN116752249B_ABST
Patent Text Reader

Abstract

The present invention relates to a binary metal magnetic separable nanocomposite fiber and a preparation method thereof, the method comprising the following steps: nanofibers are added to water and dispersed to obtain a suspension A; metal salt A and metal salt B are added to a mixed solution of water and alcohol, dispersed and placed in liquid nitrogen, and then placed in a freeze dryer to obtain a composite solid C; the composite solid C is added to the suspension A, urea is subsequently added, ammonia water is slowly dripped and stirred, placed in a reactor and reacted in an oven, the product is centrifuged and collected, and the binary metal magnetic separable nanocomposite fiber is obtained after calcination. The binary metal magnetic separable nanocomposite fiber prepared by the method of the present invention presents a fibrous material with a diameter of 10-11 μm as a whole, and the binary magnetic nanoparticles covered on the surface are uniform in size, uniformly dispersed, and have high recovery and separation efficiency; the reaction process is simple and easy to control, the reaction conditions are mild, no large-scale instruments and equipment are required, and the synthesis method has universal applicability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nanofiber preparation, and in particular to a binary metal magnetically separable nanocomposite fiber and a preparation method thereof. Background Art

[0002] Magnetic fiber is a fibrous magnetic material, and its composite material has a wide range of applications in the fields of electromagnetic conversion, electromagnetic shielding, electromagnetic memory, medical treatment, biology, separation and purification. Recyclable and separable magnetic nanocomposite fibers can be obtained by solidifying nanofibers with magnetic nanoparticles. However, it is very difficult to prepare magnetic nanofiber composite materials with uniform surface dispersion of ultra-small nanoparticles, mainly due to the serious agglomeration and aggregation between magnetic nanoparticles, which limits their further application. Therefore, in the preparation process of magnetic nanofibers, controlling the dispersion of surface magnetic nanoparticles is a prerequisite for obtaining a magnetic fiber composite material with uniform surface and high specific surface area. In addition, the simultaneous introduction of binary metal magnetic nanoparticles can effectively improve its various properties through the synergistic effect between metals. However, due to the differences in properties between various metals, the two phases are often not fused, which limits the further improvement of their performance. Therefore, the present invention develops and prepares uniformly dispersed binary magnetic nanocomposite fibers. Summary of the invention

[0003] The purpose of the present invention is to provide a binary metal magnetic separable nanocomposite fiber and a preparation method thereof, so as to solve the problem of serious agglomeration and aggregation between magnetic nanoparticles in the prior art.

[0004] In one aspect, the present invention provides a method for preparing binary metal magnetically separable nanocomposite fibers, comprising the following steps:

[0005] (1) Weigh 50-150 mg of nanofibers and add them to 30-50 mL of deionized water. Ultrasonic dispersion is performed for 5-8 h to obtain a uniformly dispersed suspension A.

[0006] (2) adding metal salt A and metal salt B to a mixed solution of water and alcohol and dispersing them uniformly to obtain a solution B with a concentration of 9 to 22 mmol / L, placing the solution B in liquid nitrogen, and then placing it in a freeze dryer, evacuating to 0.1 to 0.2 kPa, drying for 36 to 48 hours, and collecting to obtain a fluffy composite solid C;

[0007] (3) adding the composite solid C to the suspension A and magnetically stirring to obtain a suspension D, wherein the mass ratio of the composite solid C to the nanofibers is 1:2.0-5.0;

[0008] (4) adding urea to the suspension D, ultrasonicating for 20 to 35 minutes, magnetically stirring for 1 to 1.5 hours, and then slowly dropping ammonia water and stirring, wherein the mass ratio of urea to the composite solid C is 1:0.7 to 1.5, and the volume ratio of ammonia water to the suspension A is 1:0.2 to 0.8;

[0009] (5) placing the solution obtained in step (4) into the inner liner of the reaction kettle and sealing it, installing the inner liner into the outer kettle and fixing it, and then placing it in an oven, reacting at 100-130° C. for 4-8 hours. After the hydrothermal reaction is completed, the mixture is naturally cooled to room temperature, and the product is collected by centrifugation, washed alternately with water and alcohol, and placed in a vacuum drying oven for 15-24 hours to obtain an intermediate product E;

[0010] (6) The intermediate product E is placed in an alumina crucible, heated from room temperature to 450-650°C at a heating rate of 5-8°C / min under protective gas, calcined for 1-2h, cooled to room temperature, and the product is collected to obtain binary metal magnetic separable nanocomposite fibers.

[0011] Furthermore, the diameter of the nanofibers in step (1) is 5 to 15 μm.

[0012] Furthermore, the metal salt A in step (2) is one of the nitrates, hydrochlorides, acetates or sulfates of cobalt, nickel or copper; the metal salt B is a trivalent iron salt, specifically one of ferric nitrate, ferric chloride, ferric acetate or ferric sulfate, and the molar ratio of the metal salt A to the metal salt B is 1:0.8-1.2.

[0013] Furthermore, the mixed solution of water and alcohol in step (2) is a mixed solution of deionized water and anhydrous ethanol in a volume ratio of 1:0.8-1.2, the volume of the solution B placed in liquid nitrogen is 5-8 mL, and the dispersion is specifically ultrasonic dispersion, the ultrasonic power is 200-500 W, and the temperature is 25-30°C.

[0014] Furthermore, in step (2), the freezing time of solution B in liquid nitrogen is 1-2 minutes, and before solution B is placed in the freeze dryer, the opening is sealed with dust-free paper to ensure that it is fully dried under low pressure conditions.

[0015] Furthermore, in step (3), the magnetic stirring rate is 400-600 r / min, and the stirring time is 1-1.5 h.

[0016] Furthermore, in step (4), the ultrasonic power is 100-300 W, the ultrasound is carried out at a temperature of 25-30° C., the magnetic stirring rate is 200-300 r / min, the ammonia drop acceleration rate is 5-7 s / drop, the drop is added while stirring, the stirring rate is 200-300 r / min, and the stirring time is 2-3 h.

[0017] Furthermore, in step (5), the filling ratio of the solution obtained in step (4) to the inner lining of the reactor is 35-55%, and water and alcohol are alternately cleaned, filtered or centrifuged 6-10 times.

[0018] Furthermore, the protective gas in step (6) is N2 or Ar, and before starting to heat up, the protective gas is introduced for 1 to 2 hours, and the cooling rate is 2 to 5°C / min.

[0019] On the other hand, the present invention provides a binary metal magnetic separable nanocomposite fiber, wherein binary metal magnetic nanoparticles are uniformly wrapped on the surface of the nanofiber, the binary metal magnetic nanoparticles are a mixture of ferroferric oxide and any one of cobalt oxide, nickel oxide and copper oxide, the diameter of the nanofiber is 5 to 15 μm, the particle size of the binary metal magnetic nanoparticles is 5 to 200 nm, the binary metal magnetic separable nanocomposite fiber is a fibrous material with a diameter of 5 to 18 μm, and the binary metal magnetic separable nanocomposite fiber is a secondary pore structure with coexistence of micropores and mesopores, wherein the micropores are less than 2 nm and the mesopores are 2 to 10 nm.

[0020] The beneficial effects of adopting the above technical solution of the present invention are:

[0021] The present invention uses iron salt and another metal salt as composite metal precursors, a mixed solution of water and alcohol as a solvent, forms a uniform and fluffy composite metal salt by freeze drying, uses nanofibers as carriers, urea and ammonia water as precipitants, and coordinately regulates parameters such as metal salt ratio, metal salt to fiber ratio, and precipitant drop acceleration rate to achieve uniform preparation of binary metal magnetic nanocomposite fibers through a hydrothermal-calcination method. The method has a simple and easy-to-control reaction process, mild reaction conditions, and does not require large-scale instruments and equipment. The synthesis method has universal applicability, and the product is uniform, and the separation and recovery effect is good. Specifically:

[0022] 1) The method of the present invention has universal applicability, simple synthesis path, easy control, low cost, high efficiency, high product yield, and can be applied to industrial production. At the same time, the synthesis method can be extended to the preparation of multi-metal magnetic separable nanocomposite fibers;

[0023] 2) Before the metal salt precursor is compounded with the nanofiber, the precursor is mixed and freeze-dried so that the binary metal sites can be compounded uniformly and the particle size of the nanoparticles on the fiber surface can be reduced. The surface particle size of the prepared binary metal magnetically separable nanocomposite fiber is uniform and small, which is beneficial to the electron transmission between the magnetic nanoparticles and the nanofiber surface and increases the number of active sites.

[0024] 3) The metal precursor solvent used is a mixture of anhydrous ethanol and deionized water, and its polarity is used to form a droplet-shaped metal precursor, which determines the formation of smaller nanoparticles on the surface of the nanofibers;

[0025] 4) The method of the present invention forms a secondary pore structure with coexistence of micropores and mesopores. The micropores are conducive to the adsorption of the reactants, and the mesopores are conducive to the transportation of the reactants.

[0026] 5) Ammonia water is added slowly and dropwise to the suspension, so that the ultra-small particle size of the metal nanoparticles is maintained and the occurrence of side reactions is reduced;

[0027] 6) First, the nanofibers are ultrasonically dispersed, and then a metal salt precursor is added to make the binary metal ions evenly coordinate with the surface of the nanofibers, thereby forming chemical bonds, which is beneficial to the stability of the structure and accelerates the charge transfer between them;

[0028] 7) Calcination conditions play a key role in the formation of nanocomposite fibers with secondary pore structure. The calcination conditions must be under the protection of argon or nitrogen, and the heating rate must be 5 to 8 °C / min. Too fast a heating rate will lead to the agglomeration of metal particles on the fiber surface. At the same time, if the temperature is higher than 650 °C, the magnetic properties will be destroyed. If the temperature is lower than 450 °C, the mesoporous structure cannot be formed. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a low-magnification scanning electron microscope image of the product prepared in Example 1 of the present invention;

[0030] Figure 2 This is a high-magnification scanning electron microscope image of the product prepared in Example 1 of the present invention;

[0031] Figure 3 This is a scanning electron microscope image of the product prepared in Comparative Example 1 of the present invention;

[0032] Figure 4 The experimental results of separation and recovery of the product in Example 1 of the present invention under the action of a magnet are shown. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Example 1

[0034] Step 1: Weigh 100 mg of nanofibers with a diameter of 10 μm and add them to 40 mL of deionized water, and disperse them by ultrasonic for 6 h to obtain a uniformly dispersed suspension A;

[0035] Step 2: 5 mmol of copper nitrate and 5 mmol of ferric nitrate were simultaneously added to 1 L of a mixed solution of water and alcohol in a volume ratio of 1:1, and ultrasonically dispersed to obtain a solution B. 6 mL of the solution was placed in liquid nitrogen for 1 min, the opening was sealed with dust-free paper, and then placed in a freeze dryer, vacuumed to 0.1 kPa, dried for 48 h, and a fluffy composite solid C was collected;

[0036] Step 3: Add composite solid C to solution A, stir magnetically at 500 r / min, and stir for 1 h to obtain suspension D, wherein the mass ratio of composite solid C to nanofibers is 1:2;

[0037] Step 4: Take urea and add it to the suspension D, ultrasonicate for 30 minutes, magnetically stir for 1 hour, then slowly add ammonia water dropwise at a speed of 6 seconds per drop, stir while adding, the stirring rate is 200 r / min, and the stirring time is 2 hours, wherein the mass ratio of urea to composite solid C is 1:1, and the volume ratio of ammonia water to suspension A is 1:0.5;

[0038] Step 5: Place the solution obtained in step 4 into the liner of the reaction kettle and seal it. The filling ratio of the solution to the reaction liner is 40%. The liner is fixed in the outer kettle and placed in an oven. React at 120° C. for 6 hours. After the hydrothermal reaction is completed, cool to room temperature, collect the product by centrifugation, alternately centrifuge with water and alcohol for 8 times, and place it in a vacuum drying oven for 20 hours to obtain intermediate product E.

[0039] Step 6: Place the intermediate product E in an alumina crucible, heat it from room temperature to 550°C at a heating rate of 6°C / min under protective gas Ar, calcine it for 1.5h, cool it to room temperature at a rate of 3°C / min, and collect the product to obtain binary metal magnetic separable nanocomposite fibers. Example 2

[0040] Step 1: Weigh 50 mg of nanofibers with a diameter of 5 μm and add them to 30 mL of deionized water, and disperse them by ultrasonic for 5 h to obtain a uniformly dispersed suspension A;

[0041] Step 2: 5 mmol of cobalt acetate and 4 mmol of ferric chloride were simultaneously added to 1 L of a mixed solution of water and alcohol in a volume ratio of 1:0.8, and ultrasonically dispersed to obtain a solution B. 5 mL of the solution was placed in liquid nitrogen for 1 min, the opening was sealed with dust-free paper, and then placed in a freeze dryer, vacuumed to 0.1 kPa, dried for 36 h, and a fluffy composite solid C was collected;

[0042] Step 3: Add composite solid C to solution A, stir magnetically at 400 r / min, and stir for 1 h to obtain suspension D, wherein the mass ratio of composite solid C to nanofibers is 1:2;

[0043] Step 4: Take urea and add it to the suspension D, ultrasonicate for 20 minutes, magnetically stir for 1 hour, then slowly add ammonia water dropwise at a speed of 5 seconds per drop, stir while adding, the stirring rate is 200 r / min, and the stirring time is 2 hours, wherein the mass ratio of urea to composite solid C is 1:0.7, and the volume ratio of ammonia water to suspension A is 1:0.2;

[0044] Step 5: Place the solution obtained in step 4 into the inner liner of the reaction kettle and seal it. The filling ratio of the solution to the inner liner is 35%. The inner liner is fixed in the outer kettle and placed in an oven. React at 100°C for 4 hours. After the hydrothermal reaction is completed, cool to room temperature, collect the product by centrifugation, alternately centrifuge with water and alcohol for 6 times, and place it in a vacuum drying oven for 15 hours to obtain the intermediate product E.

[0045] Step 6: Place the intermediate product E in an alumina crucible, heat it from room temperature to 450°C at a heating rate of 5°C / min under protective gas Ar, calcine it for 1 hour, cool it to room temperature at a rate of 2°C / min, and collect the product to obtain binary metal magnetic separable nanocomposite fibers. Example 3

[0046] Step 1: Weigh 150 mg of nanofibers with a diameter of 15 μm and add them to 50 mL of deionized water, and disperse them by ultrasonic for 8 h to obtain a uniformly dispersed suspension A;

[0047] Step 2: 10 mmol nickel chloride and 12 mmol ferric chloride were simultaneously added to 1 L of a mixed solution of water and alcohol in a volume ratio of 1:1.2, and ultrasonically dispersed to obtain a solution B. 8 mL of the solution was placed in liquid nitrogen for 2 min, the opening was sealed with dust-free paper, and then placed in a freeze dryer, vacuumed to 0.2 kPa, dried for 48 h, and a fluffy composite solid C was collected;

[0048] Step 3: Add composite solid C to solution A, stir magnetically at 600 r / min, and stir for 1.5 h to obtain suspension D, wherein the mass ratio of composite solid C to nanofibers is 1:5;

[0049] Step 4: Take urea and add it to the suspension D, ultrasonicate for 35 minutes, magnetically stir for 1.5 hours, then slowly add ammonia water dropwise at a speed of 7 seconds per drop, stir while adding, the stirring rate is 300 r / min, and the stirring time is 3 hours, wherein the mass ratio of urea to composite solid C is 1:1.5, and the volume ratio of ammonia water to suspension A is 1:0.8;

[0050] Step 5: Place the solution obtained in step 4 into the liner of the reaction kettle and seal it. The filling ratio of the solution to the reaction liner is 55%. The liner is fixed in the outer kettle and placed in an oven. React at 140°C for 8 hours. After the hydrothermal reaction is completed, cool to room temperature, collect the product by centrifugation, alternately centrifuge with water and alcohol for 10 times, and place it in a vacuum drying oven for 24 hours to obtain intermediate product E.

[0051] Step 6: Place the intermediate product E in an alumina crucible, heat it from room temperature to 650°C at a heating rate of 8°C / min under protective gas N2, calcine it for 2 hours, cool it to room temperature at a rate of 5°C / min, and collect the product to obtain binary metal magnetic separable nanocomposite fibers. Example 4

[0052] Step 1: Weigh 50 mg of nanofibers with a diameter of 8 μm and add them to 35 mL of deionized water, and disperse them by ultrasonic for 6 h to obtain a uniformly dispersed suspension A;

[0053] Step 2: 8 mmol of cobalt nitrate and 7 mmol of ferric sulfate were simultaneously added to 1 L of a mixed solution of water and alcohol in a volume ratio of 1:1.1, and ultrasonically dispersed to obtain a solution B. 7 mL of the solution was placed in liquid nitrogen for 1.5 min, the opening was sealed with dust-free paper, and then placed in a freeze dryer, vacuumed to 0.2 kPa, dried for 40 h, and a fluffy composite solid C was collected;

[0054] Step 3: Add composite solid C to solution A, stir magnetically at 550 r / min, and stir for 1.2 h to obtain suspension D, wherein the mass ratio of composite solid C to nanofibers is 1:3;

[0055] Step 4: Take urea and add it to the suspension D, ultrasonicate for 28 minutes, magnetically stir for 1.1 hours, then slowly add ammonia water dropwise at a speed of 5 seconds per drop, stir while adding, the stirring rate is 250 r / min, and the stirring time is 2.5 hours, wherein the mass ratio of urea to composite solid C is 1:0.9, and the volume ratio of ammonia water to suspension A is 1:0.6;

[0056] Step 5: Place the solution obtained in step 4 into the liner of the reaction kettle and seal it. The filling ratio of the solution to the reaction liner is 40%. The liner is fixed in the outer kettle and placed in an oven. React at 130° C. for 7 hours. After the hydrothermal reaction is completed, cool to room temperature, collect the product by centrifugation, alternately centrifuge with water and alcohol for 8 times, and place it in a vacuum drying oven for 18 hours to obtain intermediate product E.

[0057] Step 6: Place the intermediate product E in an alumina crucible, heat it from room temperature to 600°C at a heating rate of 7°C / min under protective gas Ar, calcine it for 1.5h, cool it to room temperature at a rate of 3°C / min, and collect the product to obtain binary metal magnetic separable nanocomposite fibers. Example 5

[0058] Step 1: Weigh 120 mg of nanofibers with a diameter of 13 μm and add them to 40 mL of deionized water, and disperse them by ultrasonic for 7 h to obtain a uniformly dispersed suspension A;

[0059] Step 2: 9 mmol copper sulfate and 10 mmol iron sulfate were simultaneously added to 1 L of a mixed solution of water and alcohol in a volume ratio of 1:0.9, and ultrasonically dispersed to obtain a solution B. 6 mL of the solution was placed in liquid nitrogen for 1.5 min, the opening was sealed with dust-free paper, and then placed in a freeze dryer, vacuumed to 0.1 kPa, dried for 45 h, and a fluffy composite solid C was collected;

[0060] Step 3: Add composite solid C to solution A, stir magnetically at 450 r / min, and stir for 1 h to obtain suspension D, wherein the mass ratio of composite solid C to nanofibers is 1:4;

[0061] Step 4: Take urea and add it to the suspension D, ultrasonicate for 30 minutes, magnetically stir for 1 hour, then slowly add ammonia water dropwise at a speed of 7 seconds per drop, stir while adding, the stirring rate is 200 r / min, and the stirring time is 2 hours, wherein the mass ratio of urea to composite solid C is 1:1.2, and the volume ratio of ammonia water to suspension A is 1:0.6;

[0062] Step 5: Place the solution obtained in step 4 into the inner liner of the reaction kettle and seal it. The filling ratio of the solution to the inner liner is 55%. The inner liner is fixed in the outer kettle and placed in an oven. React at 100°C for 5 hours. After the hydrothermal reaction is completed, cool to room temperature, collect the product by centrifugation, alternately centrifuge with water and alcohol for 6 times, and place it in a vacuum drying oven for 24 hours to obtain intermediate product E;

[0063] Step 6: Place the intermediate product E in an alumina crucible, heat it from room temperature to 450°C at a heating rate of 5°C / min under protective gas Ar, calcine it for 2h, cool it to room temperature at a rate of 4°C / min, and collect the product to obtain binary metal magnetic separable nanocomposite fibers.

[0064] Comparative Example 1

[0065] Step 1: Weigh 100 mg of nanofibers with a diameter of 10 μm and add them to 40 mL of deionized water, and disperse them by ultrasonic for 6 h to obtain a uniformly dispersed suspension A;

[0066] Step 2: Add 5 mmol of copper nitrate and 5 mmol of ferric nitrate to 1 L of a mixed solution of water and alcohol in a volume ratio of 1:1, and disperse them evenly by ultrasonication to obtain solution B. Take 6 mL of the solution and put it in liquid nitrogen for 1 min to obtain substance C.

[0067] Step 3: Add substance C to solution A, stir magnetically at 500 r / min, and stir for 1 h to obtain suspension D, in which the mass ratio of substance C to nanofibers is 1:2;

[0068] Step 4: Take urea and add it to suspension D. After ultrasonic treatment for 30 minutes and magnetic stirring for 1 hour, take ammonia water and slowly add it drop by drop at a speed of 6 seconds per drop, stirring while adding. The stirring rate is 200 r / min and the stirring time is 2 hours. The mass ratio of urea to substance C is 1:1, and the volume ratio of ammonia water to suspension A is 1:0.5.

[0069] Step 5: Place the solution obtained in step 4 into the liner of the reaction kettle and seal it. The filling ratio of the solution to the reaction liner is 40%. The liner is fixed in the outer kettle and placed in an oven. React at 120° C. for 6 hours. After the hydrothermal reaction is completed, cool to room temperature, collect the product by centrifugation, alternately centrifuge with water and alcohol for 8 times, and place it in a vacuum drying oven for 20 hours to obtain intermediate product E.

[0070] Step 6: Place the intermediate product E in an alumina crucible, heat it from room temperature to 550°C at a heating rate of 6°C / min under protective gas Ar, calcine it for 1.5h, cool it to room temperature at a rate of 3°C / min, and collect the product to obtain binary metal magnetic separable nanocomposite fibers.

[0071] The binary metal magnetic separable nanocomposite fiber prepared in Example 1 of the present invention is a fibrous material with a diameter of 10-11 μm, and the surface is evenly covered with many small binary magnetic nanoparticles, such as Figure 1 As shown; the particle size of binary metal magnetic nanoparticles is 20-30nm, uniform in size, and evenly dispersed, such as Figure 2 As shown; however, in Comparative Example 1, the binary magnetic nanoparticles on the surface of the nanocomposite fiber material obtained without the freeze-drying experimental step were unevenly dispersed and uneven in size, indicating that the initial freeze-drying step is very important for forming uniformly dispersed binary magnetic nanoparticles; In addition, the binary metal magnetic separable nanocomposite fiber prepared in Example 1 was subjected to separation and recovery experiments, as shown Figure 4 As shown, the 0th time is the original mass of the material. After 6 times of experimental recycling, its recovery rate is as high as 98.5%, and the recycling and separation efficiency is high.

[0072] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing binary metal magnetically separable nanocomposite fibers, characterized in that: The steps include: (1) Weigh 50-150 mg of nanofibers and add them into 30-50 mL of deionized water, and disperse them by ultrasonic for 5-8 h to obtain a uniformly dispersed suspension A; (2) adding metal salt A and metal salt B to a mixed solution of water and alcohol and dispersing them uniformly to obtain a solution B with a concentration of 9 to 22 mmol / L, placing a certain amount of solution B in liquid nitrogen, and then placing it in a freeze dryer, evacuating to 0.1 to 0.2 kPa, drying for 36 to 48 hours, and collecting to obtain a fluffy composite solid C; Metal salt A is one of nitrate, hydrochloride, acetate or sulfate of cobalt, nickel or copper; The metal salt B is a trivalent iron salt, specifically one of ferric nitrate, ferric chloride, ferric acetate or ferric sulfate; (3) adding the composite solid C to the suspension A and magnetically stirring to obtain a suspension D, wherein the mass ratio of the composite solid C to the nanofibers is 1:2.0-5.0; (4) adding urea to the suspension D, ultrasonicating for 20 to 35 minutes, magnetically stirring for 1 to 1.5 hours, and then slowly dropping ammonia water and stirring, wherein the mass ratio of urea to the composite solid C is 1:0.7 to 1.5, and the volume ratio of ammonia water to the suspension A is 1:0.2 to 0.8; (5) placing the solution obtained in step (4) into the inner liner of the reaction kettle and sealing it, installing the inner liner into the outer kettle and fixing it, and then placing it in an oven, reacting at 100-130° C. for 4-8 hours. After the hydrothermal reaction is completed, the mixture is naturally cooled to room temperature, and the product is collected by centrifugation, washed alternately with water and alcohol, and placed in a vacuum drying oven for 15-24 hours to obtain an intermediate product E; (6) The intermediate product E is placed in an alumina crucible, heated from room temperature to 450-650°C at a heating rate of 5-8°C / min under protective gas, calcined for 1-2h, cooled to room temperature, and the product is collected to obtain binary metal magnetic separable nanocomposite fibers.

2. The method for preparing binary metal magnetically separable nanocomposite fibers according to claim 1, characterized in that: The diameter of the nanofibers in step (1) is 5 to 15 μm.

3. The method for preparing binary metal magnetically separable nanocomposite fibers according to claim 1, characterized in that: The molar ratio of the metal salt A to the metal salt B in the step (2) is 1:0.8-1.

2.

4. The method for preparing binary metal magnetically separable nanocomposite fibers according to claim 1, characterized in that: The mixed solution of water and alcohol in step (2) is a mixed solution of deionized water and anhydrous ethanol in a volume ratio of 1:0.8-1.2, the volume of the solution B placed in liquid nitrogen is 5-8 mL, and the dispersion is specifically ultrasonic dispersion, the ultrasonic power is 200-500 W, and the temperature is 25-30° C.

5. The method for preparing binary metal magnetically separable nanocomposite fibers according to claim 1, characterized in that: In the step (2), the solution B is placed in liquid nitrogen for freezing for 1-2 minutes. Before the solution B is placed in the freeze dryer, the opening is sealed with dust-free paper to ensure that it is fully dried under low pressure conditions.

6. The method for preparing binary metal magnetically separable nanocomposite fibers according to claim 1, characterized in that: In the step (3), the magnetic stirring rate is 400-600 r / min, and the stirring time is 1-1.5 h.

7. The method for preparing binary metal magnetically separable nanocomposite fibers according to claim 1, characterized in that: In the step (4), the ultrasonic power is 100-300 W, the ultrasound is carried out at a temperature of 25-30° C., the magnetic stirring rate is 200-300 r / min, the ammonia drop acceleration rate is 5-7 s / drop, the drop is added while stirring, the stirring rate is 200-300 r / min, and the stirring time is 2-3 h.

8. The method for preparing binary metal magnetically separable nanocomposite fibers according to claim 1, characterized in that: In the step (5), the filling ratio of the solution obtained in step (4) to the inner lining of the reactor is 35-55%, and water and alcohol are alternately washed, filtered or centrifuged 6-10 times.

9. The method for preparing binary metal magnetically separable nanocomposite fibers according to claim 1, characterized in that: The protective gas in step (6) is N2 or Ar. Before starting to heat up, the protective gas is introduced for 1 to 2 hours, and the cooling rate is 2 to 5°C / min.

10. A binary metal magnetically separable nanocomposite fiber obtained by the preparation method according to claim 1, characterized in that: Binary metal magnetic nanoparticles are uniformly wrapped on the surface of nanofibers. The binary metal magnetic nanoparticles are a mixture of ferroferric oxide and any one of cobalt oxide, nickel oxide and copper oxide. The diameter of the nanofibers is 5 to 15 μm. The particle size of the binary metal magnetic nanoparticles is 5 to 200 nm. The binary metal magnetically separable nanocomposite fibers are fibrous materials with a diameter of 5 to 18 μm. The binary metal magnetically separable nanocomposite fibers are secondary pore structures with coexistence of micropores and mesopores, wherein the micropores are less than 2 nm and the mesopores are 2 to 10 nm.

Citation Information

Patent Citations

  • A preparing method of acetylated nanometer cellulose-based magnetic oil-absorbing aerogel

    CN106496642A

  • NiFe2O4 / carbon nanosheet composite material and preparation method thereof

    CN109637840A